Taxation, Insurance and Precautionary Labor - Nick Netzer; Florian Scheuer (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
We examine optimal taxation and social insurance if insurance markets are imperfect. This requires the development of a theory of labor supply under uncertainty. We show that the case for social insurance is not generally reinforced by adverse selection in insurance markets as social insurance will have welfare-decreasing effects on the labor market. Furthermore, positive and normative implications are highly sensitive to the insurance market equilibrium concept. While for the Rothschild-Stiglitz case social insurance at least alleviates the inefficiency of underinsurance, with a Wilson pooling equilibrium this inefficiency might even be worsened by social insurance. This sheds new light on the question whether social insurance is an appropriate means of redistribution in the presence of an optimally chosen tax schedule.
Keywords: H50; H23; H21; J22; D81; 330; Redistributive Taxation; Social Insurance; Adverse Selection; Precautionary Labor